EVALUASI PERDA DIY NOMOR 1 TAHUN 2014 TENTANG PENANGANAN GELANDANGAN DAN PENGEMIS DI KOTA YOGYAKARTA - Ratih Latif Pramana; Istiana Hermawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Behind the glitter of big cities, there are still many dark sides, many household chores are still problematic in big cities, one of which is dealing with homeless people and beggars who are still often found in every corner of big cities. As Schawab (1992) said, homelessness and begging are still a national problem that occurs in many big cities, including in developed countries. Homeless people and beggars are generally often found at traffic lights, markets, restaurants such as restaurants, in front of retailers such as in front of supermarkets or minimarkets, at the extreme, some even enter residential areas, which in fact is quite disturbing and unsettling. As reported by Kompas.com in 2019, there were 77,500 homeless people and beggars in all big cities in Indonesia. There needs to be a mutual understanding between the people in the city of Jogjakarta with regional regulation Number 1 of 2014 Article 2 paragraph (5), so that legal regulations do not conflict with the social situation of the people of Jogja who are very easy to give and have high compassion. In this way, the author draws a problem formulation related to the Yogyakarta Special Region Regulation Number 1 of 2014 is relevant, is the implementation of the Yogyakarta Special Region Regulation Number 1 of 2014 on target and evaluation of the Yogyakarta Special Region Regulation Number 1 of 2014. The research approach used in this research qualitative with literature study research methods (Putrihapsari & Fauziah, 2020). Literature study is research carried out by reviewing various literature studies required in research (Nazir, 2014), by utilizing literature to obtain data in the field without the need to go directly to informants or the community. Library research time starts from June 5 2024 to review and search for reference sources relevant to this research. Yogyakarta Special Region Regulation Number 1 of 2014 concerning Handling Homelessness and Beggars in Yogyakarta is a concrete manifestation of the city of Yogyakarta which in fact is a cultural city, student city and a city rich in extraordinary tourist destinations that is very aware of its territory. The presence of homeless people and beggars continues to increase almost every year in the city of Jogja, causing the government to provide several strict sanctions both for homeless people and beggars and also for the general public who give money. In fact, to have a deterrent effect, these homeless people and beggars must be returned to their hometowns because they are in fact sprawled out in the city. Jogja mostly comes from outside the city of Jogja. If this is still not heeded, then the sanction of imprisonment must also be imposed, not only for money givers but also for homeless people and beggars to provide a deterrent effect.